2017
DOI: 10.1007/s10661-017-5872-z
|View full text |Cite
|
Sign up to set email alerts
|

The spatial variation of O3, NO, NO2 and NO x and the relation between them in two Swedish cities

Abstract: Ozone and nitrogen oxides (NOx) are air pollutants with known associations to adverse health effects on humans. Few studies have simultaneously measured ozone and nitrogen oxides with high spatial resolution. The main aim of this paper was to assess the levels and variation of ground-level ozone, NO2 and NOx in two Swedish cities. An additional aim was to describe the levels of these pollutants within and between three different types of measurement sites (regional background, urban background and traffic site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 30 publications
(48 reference statements)
6
32
0
2
Order By: Relevance
“…Factor 2 was characterized by high percentages of C 6 -C 7 alkanes and certain amounts of aromatics, while the contributions of other combustion tracers were insignificant in this factor, suggesting that this factor was related to solvent usage. This is consistent with previous studies that show that aromatics and C 6 -C 7 alkanes could be used as solvents in the printing and paint industry (He et al, 2002;Chan et al, 2006;Liu et al, 2008a, b); 18 ± 2 % of the observed VOCs were identified to be associated with solvent use. Factor 3 was represented by high percentages of ethane (∼ 65 %), acetylene (∼ 51 %), benzene (∼ 52 %) and ethene (∼ 31 %), together with some C 3 -C 5 alkanes and alkenes, which are typically tracers of incomplete combustion such as vehicular exhaust and biomass burning (Nelson et al, 1984;Wadden et al, 1986;Blake et al, 1994;Rudolph, 1995;Guo et al, 2011a, b).…”
Section: Source Apportionments Of Vocssupporting
confidence: 92%
“…Factor 2 was characterized by high percentages of C 6 -C 7 alkanes and certain amounts of aromatics, while the contributions of other combustion tracers were insignificant in this factor, suggesting that this factor was related to solvent usage. This is consistent with previous studies that show that aromatics and C 6 -C 7 alkanes could be used as solvents in the printing and paint industry (He et al, 2002;Chan et al, 2006;Liu et al, 2008a, b); 18 ± 2 % of the observed VOCs were identified to be associated with solvent use. Factor 3 was represented by high percentages of ethane (∼ 65 %), acetylene (∼ 51 %), benzene (∼ 52 %) and ethene (∼ 31 %), together with some C 3 -C 5 alkanes and alkenes, which are typically tracers of incomplete combustion such as vehicular exhaust and biomass burning (Nelson et al, 1984;Wadden et al, 1986;Blake et al, 1994;Rudolph, 1995;Guo et al, 2011a, b).…”
Section: Source Apportionments Of Vocssupporting
confidence: 92%
“…From the MI scores, the variables that share the highest correlation to O 3 are NOx, wind speed (WS), m,p-Xylene (TNX) and NO 2 . It is well known from previous studies [20,58,59] that O 3 is strongly connected to NO and NO 2 as well as NOx concentrations. Furthermore, TNX was found as the largest contributor to O 3 formation [55].…”
Section: Discussionmentioning
confidence: 99%
“…O 3 is often associated in urban areas with adverse effects on human health and natural environment (Hagenbjörk et al, 2017). It is well known that this secondary pollutant depends on photochemical interactions of gaseous precursors composed of nitrogen oxides (NO x ) and volatile organic compounds (VOCs) (Duan et al, 2008;WHO, 2006).…”
Section: Ozone (O 3 )mentioning
confidence: 99%
“…It is well known that this secondary pollutant depends on photochemical interactions of gaseous precursors composed of nitrogen oxides (NO x ) and volatile organic compounds (VOCs) (Duan et al, 2008;WHO, 2006). At a specific location, the level of O 3 concentration depends on emission of its precursors (VOCs and NO x ), the long-range transport of O 3 and meteorological parameters (Hagenbjörk et al, 2017). Two chemical regimes are associated with the rate of ozone production, the NO x -saturated (or VOC-limited) regime and the NO x -limited regime.…”
Section: Ozone (O 3 )mentioning
confidence: 99%